CHANGES IN THE TRIGEMINAL GANGLION OF RATS WITH ACUTE CARRAGEENAN-INDUCED INFLAMMATION - Danyliv, О.D.; Shepitko, V.I.; Yakushko, O.S.; Stetsuk, Ye.V.; Boruta, N.V. (World of Medicine and Biology, 2022)
The purpose of the study was to establish the response of the components of the trigeminal ganglion in rats to aseptic inflammation under experimental conditions. The study was performed on 40 mature white male rats. Trigeminal ganglion of rats was the object of the study. The animals were divided into two groups: the control group of animals (5), which were injected with isotonic NaCl solution and the group of experimental animals (35), which were simulated acute carrageenan-induced inflammation. The rats were sacrificed within days 3, 5, 7, 10, 14, 21, and 30 under thiopental anesthesia overdose. Histological examination showed that carrageenan-induced inflammation in the trigeminal ganglion of rats had a staged course. Reactive changes in the vessels of the hemomicrocirculatory bed were most pronounced on the 5th day of observation. After that, the blood flow gradually stabilised until its complete normalization on the 14th day. Signs of reactive changes in neurons in the form of gradual oedema of the cytoplasm and nucleus and perinuclear chromatolysis were already noticed in the early stages of the experiment. The nature of the changes intensified with the increase in the observation period. Some cells showed signs of degenerative-dystrophic processes. The proliferative activity of glial cells increased in response to changes in neurons. The signs of inflammation in the parenchyma reached their maximum manifestation on the 14th day with an incomplete regeneration process for up to the 30th day.
Keywords: trigeminal ganglion; inflammation; carrageenan; rats